Role of drug-induced sleep endoscopy in evaluation of positional vs non-positional OSA - Ming-Chin Lan; Stanley Yung-Chuan Liu; Ming-Ying Lan; Yun-Chen Huang; Tung-Tsun Huang; Yen-Bin Hsu (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The study aimed to evaluate the anatomical differences between positional and non-positional OSA, and to identify the potential predictors for distinguishing between these two types of OSA. Methods A cross-sectional study of 230 consecutive patients with OSA undergoing DISE (Drug-induced Sleep Endoscopy) was carried out at a tertiary academic medical center. The factors correlating with positional and non-positional OSA were analyzed, including clinical characteristics, polysomnography data, and DISE findings. Results Univariate analysis revealed that non-positional dependency was correlated with a higher BMI (p < 0.001), neck circumference (p < 0.001), modified Mallampati score (p = 0.003), AHI (p < 0.001), degree of velum concentric collapse (p = 0.004), degree of oropharyngeal lateral wall collapse (p < 0.001), and degree of tongue base anteroposterior collapse (p = 0.004). Multivariate analysis revealed that oropharyngeal lateral wall collapse (OR = 1.90, p = 0.027) was the only anatomical factor significantly predicted non-positional dependency in OSA patients. AHI (OR = 1.04, p < 0.001), although significant, made only a marginal contribution to the prediction of non-positional dependency. Conclusions Oropharyngeal lateral wall collapse was identified as the only anatomical predictor for non-positional dependency in OSA patients. Therefore, further treatment modalities should address the distinct anatomical trait between positional and non-positional OSA. Graphical abstract